Double blind exploratory study on de novo lipogenesis in preterm infants on parenteral nutrition with a lipid emulsion containing 10% fish oil. Issue 2 (April 2016) - Biagetti, Chiara; Vedovelli, Luca; Savini, Sara; Simonato, Manuela; D'Ascenzo, Rita; Pompilio, Adriana; Cogo, Paola E.; Carnielli, Virgilio P.
Summary: Background & aims: Provision of long chain polyunsaturated fatty acids (LCP) both of the omega-3 and omega-6 families is recommended for preterm infants (PI). Fish oil (FO) contains omega-3 and omega-6 LCP and it is incorporated in the fat blend of the new generation lipid emulsions (LE). Omega-3 LCP have been shown to reduce the expression of genes involved in lipogenesis, which could be important for several organs development. The aim of this study was to ascertain if the use of intravenous FO has an effect on lipogenesis in PI. Methods: Forty PI were randomized to receive two LE:MSF (50:40:10 Medium Chain Triglycerides (MCT): Soybean oil (SO): FO) orMS (50:50 MCT:SO). We measured plasma lipids on day 7 and the fractional and absolute synthesis rates (FSR and ASR) of cholesterol and of selected fatty acids (FA) after 2 H2 O body water labeling. Results: Plasma phospholipids (PL), free cholesterol (FC), and cholesterol esters (CE) concentrations were all lower in MSF than in MS. In spite of lower plasma FC and CE concentrations, cholesterol biosynthesis was similar between the two study groups ( FC :FSR 16.0 ± 1.4 vs 14.1  ± 1.1%/d, p  = 0.74;ASR 6.8 ± 0.6 vs 7.1 ± 0.6 mg kg −1  d −1, p  = 0.93; CE :FSR 3.6 ± 0.5 vs 4.2 ± 0.4%/d, p  = 0.38;ASR : 3.3 ± 0.4 vs 4.4 ± 0.5 mg kg −1  d −1, p  = 0.13, in MSF and MS respectively). FSR and ASR of selected FA were, or tended to be, lower in MSF than in MS. ASR of PL palmitate (4.0 ± 0.3 vs 4.8 ± 0.4 mg kg −1  d −1, p  = 0.045), PL oleate (0.2 ± 0.04 vs 0.4 ± 0.05 mg kg −1  d −1, p  = 0.02) and CE oleate (0.5 ± 0.1 vs 0.9 ± 0.1 mg kg −1  d −1, p  = 0.03) were significantly lower in MSF than in MS. There were no differences in plasma TG FA biosynthesis. Conclusions: Cholesterol biosynthesis was not affected by 10% FO during neonatal parenteral nutrition. Ten percent FO caused a statistically significant reduction in the lipogenesis of selected FA and an overall tendency towards a reduced lipogenesis. The magnitude seems to be limited and the biological significance is unknown. Our data warrant follow-up studies in PI who receive intravenous FO, especially in those infants who receive larger doses than in the present study. Since this trial started in 2007, trial registration was not required.